Solving Fuzzy Fractional Boundary Value Problems Using Fractional Differential Transform Method - Mohammed, Osama H; Ahmed, Salam A (Al-Nahrain Journal of Science, 2013)
In this paper we shall present an approximate solution for fuzzy fractional boundary value problems (FFBVP's) based on the Fractional Differential Transform Method (FDTM) which is proposed to solve linear and nonlinear FFBVP,s. The fuzziness will appear in the boundary conditions, to be fuzzy numbers. The solution of our model equations are calculated in the form of convergent series with easily computable components. Some examples are solved as an illustrations, the numerical results shows that the followed approach is easy to implement and accurate when applied to FFBVP,s.